Clinical Investigation (Neuroscience and Respiration ;, 2018)
Clinical investigation plays an essential role in the differential diagnosis, biomarker development, and therapy and cure of diseases. The book presents a bench-to-bed approach, with broad empirical coverage by experienced practitioners. The articles include topics like cytokine receptors in lung cancer, conduciveness of oxidative stress to carcinogenesis, safety and effectiveness of surgical correction of deformed chest, diagnostic and treatment regimens in inflammation-ridden obstructive lung conditions, alterations in growth hormone secretion leading to disorders of growth and metabolism, microbiota transplantation in pediatric patients, and the promising markers of renal epithelial injury. Yet another issue concerns the restructuring of chronic pain management by establishing the community-based specialized pain clinics. The book aims to disseminate and deliberate on the latest interdisciplinary medical knowledge to enhance clinical outcomes. Being a blend of clinical investigation and practice the book is addressed to physicians, scientists, and allied health care professionals.